FAMILY KNOWLEDGE AND ATTITUDES AS PREDICTORS OF ADOLESCENTS’ CLEAN AND HEALTHY LIVING BEHAVIOR (PHBS) IN BANGKALAN, INDONESIA - Sofa Qurrata A’yun; Arlia Shanti Astuti; Warda Anil Masyayih; Eny Siswati (Literasi Kesehatan Husada: Jurnal Informasi Ilmu Kesehatan, 2026)
Background: Clean and Healthy Living Behavior (PHBS) among adolescents remains a public health priority in East Java, where disparities in sanitation and household health practices persist despite ongoing national efforts. Family cognitive and affective factors—particularly knowledge and attitudes—are widely acknowledged as important determinants of adolescent health behavior; however, evidence from Bangkalan Regency remains limited. Objectives: This study aimed to analyze family knowledge and family attitudes as predictors of adolescents’ PHBS and to identify the dominant influencing factor. Methods: A cross-sectional study was conducted among 120 families with adolescents aged 12–18 years selected through probability sampling. Data were collected using a structured questionnaire validated through Pearson correlation (r > 0.361) and reliability tested using Cronbach’s Alpha (knowledge = 0.81; attitude = 0.85; PHBS = 0.79). Data analysis included univariate distribution, Chi-square tests, and multivariate logistic regression with a significance level of 0.05. Results: A total of 63% of families demonstrated good knowledge of PHBS, 58% had positive attitudes, and 60% of adolescents practiced good PHBS. Family knowledge was significantly associated with adolescent PHBS (p = 0.021), as was family attitude (p = 0.008). Logistic regression revealed that family attitude was the dominant predictor (OR = 2.87; 95% CI: 1.31–6.28; p = 0.006), while family knowledge remained significant (OR = 1.94; 95% CI: 1.02–3.71; p = 0.039). The model explained 32% of the variance in adolescent PHBS (Nagelkerke R² = 0.32). Conclusion: Both knowledge and attitudes of families significantly influence adolescents’ PHBS, with attitudes serving as the strongest predictor. Strengthening family-based health promotion—particularly those targeting attitude change and supportive household norms—is essential for improving sustainable adolescent health behavior in Bangkalan.